A Thematical Study on the Influence of Online Retailer’s Characteristics in E-commerce - Kandambi, G. P. H.; Wijayanayake, W. M. J. I. (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
The transaction between buyer and seller has changed due to the technological advancement of the Internet and socio-economic activities. The desire to visit a physical shop has been replaced by online purchasing, and retailers can now easily reach international markets from their local base without the need for retail space or warehousing. As a result, the market price is penetrated. In online purchasing, the vendor plays an important role. This assessment focuses on the characteristics of retailers that influence online purchasing. The assessment will lay the groundwork for determining the gap and its scope for future research. This study was evaluated using a thematic analytical approach. Between 2010 and 2015, forty-three (n=43) leading and peer-reviewed conferences and indexed journals were used in the evaluation. Based on their working definitions, ten (n=10) sub-themes were recognised from the investigated variables. The product's and price's moderating abilities must be investigated, despite the fact that they are critical factors in online purchasing. Online shopping is popular in society because it has several advantages over traditional shopping. Since virtual products and actual things cannot be used in conjunction with one another, it is necessary to investigate each product category independently when buying online. The characteristics of retailers and their unclear antecedents require further attention in future research. Future studies should use a thorough integrated model to examine a wider range of variables.